Peningkatan Kompetensi Guru dalam Pengembangan Modul Ajar Kurikulum Merdeka Berbasis Project Based Learning Melalui Pemanfaatan Artificial Intelligence di SD Laboratorium UM Kota Malang - Dewi, Radeni Sukma Indra; Kusumaningrum, Shirly Rizki; Mardhatillah, Mardhatillah; Faizah, Siti; Ekawati, Ratna; Fitriyah, Siti Ni’matul; Mufidah, Siti; Islami, Kaisra Alfikri; Effendi, Muhammad Idris (Universitas Nusantara PGRI Kediri, 2025)
The rapid advancement of the Fourth Industrial Revolution has introduced significant challenges in the educational sector, particularly in integrating Artificial Intelligence (AI) into teaching and learning processes. This community service program aimed to enhance the competencies of teachers at SD Laboratorium Universitas Negeri Malang (UM) in developing teaching modules based on Project-Based Learning (PjBL) integrated with AI tools, aligning with the principles of the Kurikulum Merdeka. The program encompassed a needs assessment, coordination with school leadership, preparation of training materials, and the implementation of direct training sessions focusing on the use of AI tools such as ChatGPT, Magic School, and Jenni AI in designing PjBL modules. Evaluation through questionnaires indicated a significant improvement in teachers' understanding and ability to integrate AI into their teaching modules. As a result, teachers successfully developed comprehensive PjBL-based teaching modules incorporating AI, which are expected to enhance the quality of education and foster 21st-century skills among students.